Comparison of growth performance of Nile tilapia (Oreochromis niloticus) fingerlings fed different inclusion levels of black soldier fly (Hermetia illucens) pre-pupae meal diets and its effect on the physical characteristics of the feed - Groenewald, Niklaas Jakobus (Stellenbosch : Stellenbosch University, 2018)
Thesis (MSc)--Stellenbosch University, 2018.